What drives the vacancy rate for information technology workers? - Martin Falk (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper provides empirical evidence on both the magnitude and determinants of unfilled positions for information technology workers using cross-sectional data on 4150 German firms. Vacancies are defined as unfilled positions excluding those created by replacement needs during the first half of the year 2000. The share of unfilled positions created by replacement needs is only about 20 percent, indicating that high turnover rates are not the main reason for high vacancy rates. The adjusted job vacancy rate for ICT workers varies between 5.7 percent in the ICT sector and 6.7 percent in the non-ICT sector. The results of a generalized tobit model show that the adjusted vacancy rate mainly depends on the firm size, the share of ICT workers and actions taken in the past to solve the ICT worker shortage but not on the diffusion of ICT. In the ICT sector, the decision made in the past to train apprentices in the new ICT occupations seems to have reduced the current vacancy rate. In the non-ICT sector, a successful strategy to solve the ICT worker shortage appears to be increased internal training. Finally, in the non-ICT sector, the common practice of completely outsourcing software programming significantly reduces the probability of unfilled positions. – – Dieser Beitrag beschäftigt sich mit der Anzahl und den Bestimmungsfaktoren unbesetzter Stellen für IKT-Fachkräfte in Deutschland. Datengrundlage ist eine repräsentative telefongestützte (CATI) Umfrage von 4150 Unternehmen für das Jahr 2000. Die Quote unbesetzter Stellen für IKT-Fachkräfte (ohne Stellen aufgrund Ersatzbedarfs) variiert zwischen 5,7 Prozent in der IKT-Branche und 6,7 Prozent in der Nicht-IKT-Branche. Der Anteil fluktuationsbedingt unbesetzter Stellen an allen unbesetzten Stellen beträgt 20 Prozent. Somit dürfte die Personalfluktuation der IKT-Fachkräfte nicht die Hauptursache für die hohe Quote unbesetzter Stellen sein. Regressionsergebnisse auf Basis verallgemeinerter tobit-Modelle zeigen, dass die Quote unbesetzter Stellen hauptsächlich von der Firmengröße, dem Anteil der IKT-Fachkräfte im Vorjahr sowie den Strategien zur Überwindung des IKTFachkräftemangels in der Vergangenheit abhängen, jedoch von der Diffusion der Informationstechnologie nicht beeinflusst werden. Hinsichtlich der Wahrscheinlichkeit unbesetzter Stellen zeigt sich, dass die Auslagerung der Software-programmierung an Fremdunternehmen zu einer geringeren Betroffenheit von unbesetzten Stellen für IKT-Fachkräfte führt.
Keywords: J21; O33; J63; 330; unbesetzte Stellen; IKT-Fachkräfte; Informationstechnologie; Unfilled positions; ICT workers; information technology; EDV-Berufe; Informatiker; Offene Stellen; Betriebsgröße; Betriebliche Weiterbildung; Outsourcing; Deutschland